Agroecologia, mercado e inovação social: o caso da Rede Ecovida de Agroecologia - Oscar José Rover (Ciências Sociais Unisinos)
The article analyzes the case of the Ecovida Agroecological Network, understanding that it innovates in its organizational structure and dynamics as well as in its relationship with the markets. It is organized in a multidirectional network, with horizontal and decentralized decision-making processes. Its relationship with the markets emerged from local and regional experiences. The network resisted to relate with large retail outlets (supermarkets) and created its own circuit of trade, by exchanging products between its regional centers, with promising commercial results. These innovative processes are analyzed through the theory of symbolic sites of belonging, according to which the economy is one of the components of social life and organizational dynamics, even economic ones, cannot be analyzed from a narrow mercantile mentality. Commercial exchanges are a significant dimension of social life, but the study showed that in the case of the Ecovida Agroecological Network they are not the only one, nor even the most central one.